2017
DOI: 10.1002/brb3.727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lamotrigine on seizure development in a rat pentylenetetrazole kindling model

Abstract: IntroductionEpileptogenesis is a process of seizure development. Lamotrigine is a novel antiepileptic drug which is also used for antiepileptogenic research. Kindling models are recommended as potentially useful tools for antiepileptogenic treatment discovery. However, previous studies demonstrated that the antiepileptogenic effect of lamotrigine is controversial in the electrical kindling model. Chemical kindling such as with pentylenetetrazole is another kindling model. The aims of this study were to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Neuronal damage associated with PTZ-induced kindling may be a possible consequence of recurrent seizure activity ( 60 ). In this study, histopathological results from Nissl staining showed significant neuronal damage in the CA1 area in the PTZ group, which is in agreement with previous studies ( 61 , 62 ). However, fisetin administration provided significant protection against hippocampal neuronal damage in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Neuronal damage associated with PTZ-induced kindling may be a possible consequence of recurrent seizure activity ( 60 ). In this study, histopathological results from Nissl staining showed significant neuronal damage in the CA1 area in the PTZ group, which is in agreement with previous studies ( 61 , 62 ). However, fisetin administration provided significant protection against hippocampal neuronal damage in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
“…staining showed significant neuronal damage in the CA1 area in the PTZ group, which is in agreement with previous studies (61,62). However, fisetin administration provided significant protection against hippocampal neuronal damage in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 92%
“…Our results with LTG are difficult to be compared with those achieved by kindling models of TLE, and in some studies (Stratton et al, 2003;Chen et al, 2017), antiepileptogenesis or disease modifying effects were suggested. However, in the kindling models, LTG has been administered immediately prior to the electrical or chemical kindling sessions (Stratton et al, 2003;Postma et al, 2000;Chen et al, 2017), therefore, antiepileptic effects were evaluated.…”
Section: Discussionmentioning
confidence: 59%
“…Our results with LTG are difficult to be compared with those achieved by kindling models of TLE, and in some studies (Stratton et al, 2003;Chen et al, 2017), antiepileptogenesis or disease modifying effects were suggested. However, in the kindling models, LTG has been administered immediately prior to the electrical or chemical kindling sessions (Stratton et al, 2003;Postma et al, 2000;Chen et al, 2017), therefore, antiepileptic effects were evaluated. Sometimes antiepileptogenic effects were suggested based on the results obtained after a wash-out period, however, they might be fully or partly explained by an antiepileptic action since the intensity of the kindled seizures might be less (curtailing) due to the administration of LTG prior to kindling; consequently, epileptogenesis might be slower.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation